2009
DOI: 10.1093/pcp/pcp122
|View full text |Cite
|
Sign up to set email alerts
|

Peptidyl–Prolyl Isomerase Activity in Chloroplast Thylakoid Lumen is a Dispensable Function of Immunophilins in Arabidopsis thaliana

Abstract: Chloroplast thylakoid lumen of Arabidopsis thaliana contains 16 immunophilins, five cyclophilins and 11 FK506-binding proteins (FKBPs), which are considered protein folding catalysts, although only two of them, AtFKBP13 and AtCYP20-2, possess peptidyl-prolyl cis/trans isomerase (PPIase) activity. To address the question of the physiological significance of this activity, we obtained and characterized Arabidopsis mutants deficient in the most active PPIase, AtFKBP13, and a double mutant deficient in both AtFKBP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
34
0
2

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
4

Relationship

2
8

Authors

Journals

citations
Cited by 38 publications
(37 citation statements)
references
References 47 publications
1
34
0
2
Order By: Relevance
“…Immunoblotting was performed as described previously in Ingelsson et al (2009) and Shapiguzov et al, (2010) by sodium dodecyl sulfate-polyacrylamide gel electrophoresis using 10% acrylamide gels. Antibodies against HA and P-Thr were purchased from Cell Signaling Technology (Danvers, MA).…”
Section: Immunoblottingmentioning
confidence: 99%
“…Immunoblotting was performed as described previously in Ingelsson et al (2009) and Shapiguzov et al, (2010) by sodium dodecyl sulfate-polyacrylamide gel electrophoresis using 10% acrylamide gels. Antibodies against HA and P-Thr were purchased from Cell Signaling Technology (Danvers, MA).…”
Section: Immunoblottingmentioning
confidence: 99%
“…Earlier yeast two-hybrid work by Gupta et al [64] found that Rieske interacted specifically with the AtFKBP13 signal peptide and the authors proposed a role for AtFKBP13 as a stromal regulator of Rieske assembly. This has been recently challenged by the absence of Rieske over-accumulation in an atfkbp13 knockout mutant [61] and by our finding that Rieske interacts with the mature, lumenal form of TaFKBP13, and not with its chloroplast precursor [63]. The functional significance of the FKBP13-Rieske interaction is currently unknown.…”
Section: Interactions Regulating Photosynthetic Membrane Assemblymentioning
confidence: 99%
“…Isolated proteins were also separated on SDS-PAGE and the presence of pTAC16 in the samples was analyzed by immunoblotting. Immunoblotting was performed as described before [22]. Polyclonal antibody to pTAC16 was raised against a synthetic peptide corresponding to residues 454-467 of the full pTAC16 sequence (Innovagen, Lund, Sweden).…”
Section: Dnase Treatment Of Nucleoids and Immunoblotting Analysismentioning
confidence: 99%